CrOx-promoted Ru/Al2O3 for CO2 methanation: Formation of surface Cr-doped RuO2 solid solution plays key roles. (1st May 2023) - Zhang, Zhiqiang; Deng, Shaorong; Fang, Xiuzhong; Xu, Junwei; Xu, Xianglan; Wang, Xiang
Graphical abstract: Highlights: Ru/7%CrOx /Al2 O3 was prepared via a step impregnation method and used for CO2 methanation. Cr-doped RuO2 surface solid solutions formed on the fresh RuO2 /7%CrOx /Al2 O3 . Smaller Ru sizes and stronger metal-support interaction presented for Ru/7%CrOx /Al2 O3 . The turnover frequency on Ru/7%CrOx /Al2 O3 at 200 °C was 13.6 times higher than that on Ru/Al2 O3 . The CrOx modification promoted the conversion of CO and formates. Abstract: The Ru catalysts supported on CrOx -modified Al2 O3 with varied Cr amounts were prepared via a step impregnation method and used for CO2 methanation. For fresh RuO2 /x%CrOx /Al2 O3 samples, part of Cr 3+ and Cr 6+ cations on the Al2 O3 support surface were dissolved the RuO2 lattice to form a solid solution structure by reactions between the precursor of RuO2 and the high dispersed CrOx . This structure significantly retarded the crystallization of RuO2 and the aggregation of Ru during reduction, thus significantly decreasing the size of Ru nanoparticles and enhancing the metal-support interaction in reduced Ru/x%CrOx /Al2 O3 catalysts. Consequently, the turnover frequency of CO2 on the best Ru/7%CrOx /Al2 O3 catalyst at 200 °C was 0.15 s −1, 13.6 times higher than that on Ru/Al2 O3 . The in situ FTIR spectra results demonstrate that Ru/7%CrOx /Al2 O3 possessing much higher activity than Ru/Al2 O3 can be attributed to formation of the linear-CO* with higher CO hydrogenation activity and conversion of the formates for CO2 methanation on Ru/7%CrOx /Al2 O3 .